1997
DOI: 10.1007/s004380050488
|View full text |Cite
|
Sign up to set email alerts
|

The two β-lactamase genes of Streptomyces cacaoi, blaL and blaU, are under the control of the same regulatory system

Abstract: The production of beta-lactamase in Streptomyces cacaoi, which contains two beta-lactamase-encoding genes, blaL and blaU, is inducible by beta-lactam compounds. The two genes have been cloned independently in S. lividans TK24, a beta-lactamase-negative species. The blaU clone did not respond to the presence of beta-lactams, whereas the blaL clone appeared to be inducible in S. lividans. The latter clone contains two open reading frames, blaA and blaB, located just upstream of but transcribed divergently from b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Regulation of ␤-lactamase synthesis has been studied in certain other gram-positive bacteria (11,36). In Streptomyces cacaoi, the expression of ␤-lactamase genes is controlled by a regulatory protein, BlaB (22), and mutations in blaB can lead to silencing or constitutive expression of ␤-lactamase genes (30). Homologs of bla regulators are present in the B. anthracis genome, but they are not linked to either bla gene.…”
mentioning
confidence: 99%
“…Regulation of ␤-lactamase synthesis has been studied in certain other gram-positive bacteria (11,36). In Streptomyces cacaoi, the expression of ␤-lactamase genes is controlled by a regulatory protein, BlaB (22), and mutations in blaB can lead to silencing or constitutive expression of ␤-lactamase genes (30). Homologs of bla regulators are present in the B. anthracis genome, but they are not linked to either bla gene.…”
mentioning
confidence: 99%
“…In S. cacaoi, blaU is also inducible by i-lactams, and its promoter region is very similar to that of blaL. The control of blaU also relies on the blaA and blaB genes [19].…”
Section: Regulation In Gram-positive Bacteriamentioning
confidence: 95%
“…They are also located upstream of and diverge from the controlled structural gene, blaL. BlaA is a transcriptional activator, belonging to the LysR family, and binds to the intergenic region, blaA-blaL [19] at the level of a T-N 11 -A motif, as described in Goethals et al [20]. The function of the product of blaB remains unknown.…”
Section: Regulation In Gram-positive Bacteriamentioning
confidence: 99%
“…It binds to DNA through a helix-turn-helix motif and recognizes a T-N 11 -A sequence including a double overlapping palindromic sequence [17]. This motif, characteristic of the LysR-type promoters, is present in the blaA-blaL intergenic region and upstream of blaU [14,16]. To date, no function has been attributed to BlaB.…”
mentioning
confidence: 96%
“…S. cacaoi possesses two different unlinked b-lactamase structural genes called blaL and blaU [9]. The two genes encode two extracellular active-site serine class A b-lactamases sharing 50 % strict identities [9 -13] and they are under the control of the same regulatory system [14]. Sequence analysis and genetic study of the blaL regulatory region identified two genes, blaA and blaB, located just upstream of blaL but transcribed divergently and required for the induction and for the basal expression of BlaL and BlaU [8,15,16].…”
mentioning
confidence: 99%